Ruptured axillary artery pseudoaneurysm following an anterior glenohumeral dislocation: A case report - Diogo Rocha Carvalho; José Oliveira-Pinto; António Neves; Joana Pimenta Santos; João Rocha Neves; João Torres (Orthopedic Reviews, 2020)
Vascular injuries following anterior shoulder dislocations are rare, with an estimated incidence of 1-2%. The formation of an axillary artery pseudoaneurysm secondary to vascular trauma is a possible late complication and frequently underdiagnosed since it may remain asymptomatic for many years. A rupture of a pseudoaneurysm may occur either from the dislocation itself or after forceful reduction attempts. A ruptured pseudoaneurysm of the axillary artery is a medical emergency and may result in significative upper-limb morbidity or even patient mortality. Nowadays, endovascular techniques have progressively gained ground for the treatment of such lesion, especially in an emergency context. In the present article, the authors present the case of a 77-years-old male patient with a rupture of a pseudoaneurysm of the left axillary artery after repeated forceful reductions of an anterior glenohumeral dislocation and its treatment with percutaneous endovascular stenting.